Pharmaceutical and Physico-Chemical Study of Shilajit Bhasma (International Journal of Ayurveda and Pharma Research, 2024)
Although there were mention of Shilajit Bhasma (Calx) in various classical texts, but no specific study or usage of the same found mention in Google Scholar, ARD, Pub-Med, NCBI, AYUSH Research Portal and other open source database. This study is intended for preparation of Shilajit Bhasma (Calx) and assessments of physico-chemical properties of the same. Methods: The Bhasma (Calx) of Shilajit was being prepared using classical references, from Shilajit purified with two different methods, namely, Ushna Jal Shodhita Shilajit (Agnitapi) and Triphala Kwatha (decoction) Shodhit Shilajit (Suryatapi). Main constituents used in Marana (incineration) were purified Gandhak (sulphur), Haritala (orpiment), Manasila (realgar) in equal proportion to Shilajit. IEC No. for the study is IEC-RAC-18/R.S.B.K.-18-M.D.(Ayu.). Results: Result of the FE-SEM shows that both samples contain crystalline of nano size, with size ranged from 100nm – 1µm, with irregular shape and sizes. The findings of FE-SEM are in concordance to results of classical examinations of Bhasma (Calx). XRD intensity plots of both samples show various sharp and small peaks, when diffraction patterns were observed at different 2ɵ angles ranges from 10° to 70°, various peaks identified to correspond with known peaks for S & AsS and have been marked on the plots. ICP-MS and flame photometry of both samples reveals the presence of Na, Ca, K, Mg, Mn & As in different ratio. Conclusions: It has been concluded that the elemental composition of Shilajit Bhasma have a strong similarity with Purified Shilajit.